Socio-Pedagogical Prevention Program of High-School Students’ Propensity to Virtual Social Networks’ Dependence: The Results of Program Implementation - Potomkina, Nanuli; Ryzhanova, Alla (Pedagogika, 2024)
The article presents the outcomes of a socio-pedagogical prevention program aimed at reducing high schoolers' propensity to virtual networks dependence. The results by control diagnostics showed a reduction in students' propensity on virtual networks, reflected in several indicators, including improved understanding of cyber risks, positive self-perception in both real and virtual environments, reduced interest in harmful online activities, and enhanced self-regulation and time management online.